Psikoedukasi Tentang Pengendalian Emosi dan Mencegah Tindakan Bullying Pada Siswa Kelas X Jurusan Desain Komunikasi Visual 2 SMK Bina Karya Mandiri - Syifa Zam Zami Nurjono; Farhan Yazid; Yunisa Larasati; Chintia Devi Johan; Muhammad Fadli Ayyubi; Ferdy Muzzamil (CV. ITTC INDONESIA, 2025)
Education in Vocational High Schools (SMK) plays a vital role not only in developing technical skills but also in shaping character and emotional handling, particularly among adolescents who are vulnerable to internal conflicts. This study was conducted among tenth-grade students of the Visual Communication Design 2 program at SMK Bina Karya Mandiri with the aim of providing psychoeducation on emotional handling and bullying prevention. The intervention was delivered in a single 90-minute session using a classical (lecture-based) approach, involving 38 students. The methods applied included lectures, group discussions, question-and-answer sessions, ice-breaking activities, and psychodrama to promote character development, empathy, and self-control. The results showed an increase in students' understanding of the importance of managing emotions in a healthy manner, recognizing various forms of bullying, and raising awareness of its negative impacts.